Does International Humanitarian Law Play Any Role in Demilitarized Countries? A Policy Analysis of Costa Rica and Panama - Méndez Barquero, Juan C. (2012)
This  article  reviews  the  role  of  International  Humanitarian  Law  (IHL)  in  demilitarized  countries  with  a  case  study of Costa Rica and Panama, two  small Central American countries that  have  constitutionally  abolished  their  armies. The paper addresses the question of whether a country that has not  a regular army can in fact be respectful and supportive of the international rules governing armed conflicts. Through  a  detailed  review  of  national  bodies and legislation in both countries,  the findings allow the author to conclude that the lack of regular armies or military forces is not a convincing argument to  disobey and ignore the norms of IHL.